Molecular dynamics-based identification of novel natural mortalin–p53 abrogators as anticancer agents. (2nd January 2017) - Nagpal, Neha; Goyal, Sukriti; Dhanjal, Jaspreet Kaur; Ye, Liu; Kaul, Sunil C.; Wadhwa, Renu; Chaturvedi, Rupesh; Grover, Abhinav
Abstract: Introduction : Cancer is one of the leading causes of mortality worldwide that requires attention in terms of extensive study and research. Eradication of mortalin–p53 interaction that leads to the inhibition of transcriptional activation or blocking of p53 from functioning as a suppressor and induction of nuclear translocation of p53 can prove to be one of the useful approaches for cancer management. Results : In this study, we used structure-based approach to target the p53-binding domain of mortalin in order to prevent mortalin–p53 complex formation. We screened compounds from ZINC database against the modeled mortalin protein using Glide virtual screening. The top two compounds, DTOM (ZINC 28639308) and TTOM (ZINC 38143676) with Glide score of −12.27 and −12.16, respectively, were identified with the potential to abrogate mortalin–p53 interaction. Finally, molecular dynamics simulations were used to analyze the dynamic stability of the ligand-bound complex and it was observed that residues Tyr196, Asn198, Val264 and Thr267 were involved in intermolecular interactions in both the simulated ligand-bound complexes, and thus, these residues may have a paramount role in stabilizing the binding of the ligands with the protein. Conclusion : These detailed insights can further facilitate the development of potent inhibitors against mortalin–p53 complex.